COGNITIVE METAPHORS IN POLITICAL SPEECHES: A CRITICAL DISCOURSE ANALYSIS (Лучшие интеллектуальные исследования, 2025)
Annotation: This article explores the use of cognitive metaphors in political speeches through the lens of Critical Discourse Analysis (CDA). Political language is rich in metaphorical expressions that serve cognitive, rhetorical, and ideological functions. Drawing on Conceptual Metaphor Theory and discourse-analytical frameworks, the paper examines how metaphors shape public perception, frame national issues, and reinforce ideologies in English-language political discourse. The findings highlight that metaphors such as “the nation as a family” or “war against problems” are not merely stylistic devices but tools for persuasion, identity construction, and power negotiation.